Plasma C5a and serum C5aR levels in patients with chronic spontaneous urticaria: A single-center case-control study - Thao T. Pham; Minh N. Vu; My H. Le; Doanh H. Le; Thuong V. Nguyen; Phuong T.M. Pham (PLoS ONE, 2026)
Background C5a and its receptor, C5aR, are involved in the degranulation of mast cells and basophils, leading to the release of proinflammatory cytokines. However, to date, their roles in the pathogenesis of chronic spontaneous urticaria (CSU) remain incompletely understood. Objective To investigate the association of plasma C5a and serum C5aR with disease severity in Vietnamese patients with CSU. Methods A case-control study was conducted involving 146 patients with CSU and 30 healthy adults matched by age and sex (the matching ratio ~ 5:1), at the Urticaria clinic, National Hospital of Dermatology and Venereology, Vietnam. Plasma C5a and serum C5aR levels were measured using the ELISA technique, and disease severity was assessed using the Urticaria Activity Score over 7 days (UAS7). The associations between C5a/C5aR with disease severity and several patient’s characteristics were evaluated using Spearman’s correlation and logistic regression. Results Plasma C5a levels were significantly increased in CSU patients compared to healthy controls (p < 0.001), whereas serum C5aR levels in CSU patients were significantly reduced (p < 0.001). A significant positive correlation was found between disease severity based on UAS7 scores and plasma C5a levels (Spearman’s rho = 0.63, p < 0.001), but not for serum C5aR levels (Spearman’s rho = 0.05, p = 0.527). A C5a level of 4335 pg/mL was defined as the optimal cutoff points for identifying severe CSU with an AUC of 0.86 (95% CI: 0.80–0.92, p < 0.001), sensitivity of 64%, and specificity of 100%. Several factors were found to be associated with C5a and C5aR levels, such as prothrombin time and anti-TPO antibodies. Conclusions CSU patients demonstrate elevated plasma C5a and reduced serum C5aR levels compared to healthy controls. While plasma C5a may serve as a potential biomarker for indicating CSU severity, C5aR levels show no significant association with the disease severity.